Between GDP, Inflation, and Exchange Rate: Determinants Analysis Of Indonesia's Crumb Rubber Export Volume (2013–2023) - Ni Putu Aninda Putri; Putu Krisna Adwitya Sanjaya (International Journal of Management Research and Economics, 2025)
According to BPS (2023), the increasing global demand for crumb rubber presents an opportunity for Indonesia as one of the world's leading rubber producers. Therefore, analyzing the factors affecting crumb rubber export volume is crucial. This study aims to identify and analyze the effects of the Gross Domestic Product (GDP) of Indonesia's main crumb rubber export destinations, inflation in these destination countries, and the US dollar exchange rate, both partially and simultaneously, on Indonesia’s crumb rubber export volume. The primary export destination countries examined in this study are Japan, China, India, South Korea, and Brazil. This research employs a quantitative descriptive analysis technique using secondary time-series data from 2013 to 2023. The study applies multiple linear regression analysis based on the Generalized Least Squares (GLS) method. The results indicate that GDP, inflation, and the US dollar exchange rate have a significant simultaneous impact on Indonesia’s crumb rubber export volume to its main destination countries. Partially, inflation has a significant negative effect, whereas GDP and the US dollar exchange rate have a significant positive impact on the export volume. Based on these findings, the authors recommend that the government and exporters pay close attention to per capita GDP and the USD exchange rate.